2013
DOI: 10.1128/jvi.01154-13
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Type 58 Genome Variations and RNA Expression in Cervical Lesions

Abstract: cHuman papillomavirus type 58 (HPV58) is relatively prevalent in China and other Asian countries. In this study, the HPV58 genome in cervical lesions was decoded from five grade 2 or 3 cervical intraepithelial neoplasia lesion (CIN2/3) samples and five cervical cancer tissues using rolling-circle amplification of total cell DNA and deep sequencing and verified by whole-genome cloning and sequencing. HPV58 isolates from China feature a total of 52 nucleotide substitutions (0.66%) from the reference HPV58 sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 32 publications
2
29
0
Order By: Relevance
“…In this regard, numerous studies have demonstrated that the epidemiologically high‐risk HPV16 E6 Asian‐American (AA) variant conferred a higher carcinogenic potential and, unlike other variants, its overexpression is sufficient to immortalize and transform primary human keratinocytes in the absence of E7 . In contrast to HPV16, studies on HPV58 biology are scarce . The only study on HPV58 variant available was performed to compare the transcriptional activity of the long control region of three HPV58 variants, and found that substitution of guanine to adenine residue at nucleotide position 7788 enhanced E6/E7 bistronic transcript promoter activity .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, numerous studies have demonstrated that the epidemiologically high‐risk HPV16 E6 Asian‐American (AA) variant conferred a higher carcinogenic potential and, unlike other variants, its overexpression is sufficient to immortalize and transform primary human keratinocytes in the absence of E7 . In contrast to HPV16, studies on HPV58 biology are scarce . The only study on HPV58 variant available was performed to compare the transcriptional activity of the long control region of three HPV58 variants, and found that substitution of guanine to adenine residue at nucleotide position 7788 enhanced E6/E7 bistronic transcript promoter activity .…”
Section: Discussionmentioning
confidence: 99%
“…36 In contrast to HPV16, studies on HPV58 biology are scarce. 22,23 The only study on HPV58 variant available was performed to compare the transcriptional activity of the long control region of three HPV58 variants, and found that substitution of guanine to adenine residue at nucleotide position 7788 enhanced E6/E7 bistronic transcript promoter activity. 37 Our current study represents the very first investigation to describe and compare the oncogenic properties of the three most common naturally occurring HPV58 E7 variants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HPV 58 accounts for a considerable disease burden in East Asia. Its prevalence in cervical cancer is higher in Asia (5.6%) than in other parts of the world (3.3%) [13]. In a large scale Korean study (n=1,650), HPV 58 was the second most common HPV in LSIL (8.1%) and HSIL (15.7%) [14].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of HPV 58 increases significantly according to the severity of cervical neoplasia, and its variants are epidemiologically associated with a higher oncogenic risk [11]. Four featured variant lineages of HPV 58 (sublineage A1) showing a regional preponderance in Asia, and associated with a higher risk for cervical neoplasia, were recently reported [13,25]. Therefore, the detection of HPV 58 in addition to HPVs 16 and 18 in cytologically abnormal women may provide an early indicator of cervical precancerous lesion and invasive cancers in East Asia.…”
Section: Discussionmentioning
confidence: 99%